1992
DOI: 10.1038/ki.1992.59
|View full text |Cite
|
Sign up to set email alerts
|

Focal glomerulosclerosis in idiopathic membranous glomerulonephritis

Abstract: The significance of the finding of focal glomerulosclerosis (FGS) in idiopathic membranous glomerulonephritis (MGN) is uncertain. Twenty-seven patients with mixed FGS and MGN (MGN-FGS) were compared to 25 patients with MGN alone (generally matched for age, sex and stage of glomerular lesion) with respect to pathology, presenting clinical and laboratory features, and course of disease. Biopsies from the MGN-FGS patients showed significantly more extensive tubulointerstitial disease (P less than 0.001) than did … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
42
1

Year Published

1996
1996
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(48 citation statements)
references
References 36 publications
5
42
1
Order By: Relevance
“…Also new are data suggesting that the configuration of the immune composite on electron microscopy may be of help in indicating those who are most likely to respond to treatment. Patients with homogeneous electron dense deposits, i.e., synchrony of the deposits at a single stage, do better than patients with heterogeneous (multistage) deposits on electron microscopy (19,20).…”
Section: Pathologymentioning
confidence: 99%
“…Also new are data suggesting that the configuration of the immune composite on electron microscopy may be of help in indicating those who are most likely to respond to treatment. Patients with homogeneous electron dense deposits, i.e., synchrony of the deposits at a single stage, do better than patients with heterogeneous (multistage) deposits on electron microscopy (19,20).…”
Section: Pathologymentioning
confidence: 99%
“…A total of seven studies, including the present study, fulfilled the inclusion criteria [9][10][11][12]14,15] All studies were retrospective by design. Detailed data of one study were unavailable [14].…”
Section: Meta-analysis Of Studies Analysing the Prognostic Significanmentioning
confidence: 99%
“…In previous studies, we have found that urinary b2-microglobulin (b2M) accurately predicts prognosis in patients with iMN [6][7][8]. Recent studies have provided evidence that morphological parameters-specifically focal segmental glomerulosclerosis (FSGS)-may be used as prognostic parameter [9][10][11][12]. In the present study, we have evaluated FSGS as prognostic parameter in patients with iMN.…”
Section: Introductionmentioning
confidence: 99%
“…Histological staging was based on histological lesion, including glomerular lesion, 15 tubulointerstitial lesion, focal glomerulosclerosis, 16 and fibrointimal lesion. Biopsy specimens were reviewed by a nephropathologist unaware of patients' clinical history, renal function, and IL-6 gene SNP (C-572G).…”
Section: Renal Biopsy Reviewmentioning
confidence: 99%